Biomarkers of gastric atrophy at stomach cancer - A. V. Belkovets; S. A. Kurilovich.; Yu. I. Ragino; L. V. Scherbakova; O. B. Cheremisina; N. V. Cherdyntseva; N. A. Andryushina; M. I. Voyevoda (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Background. Atrophic gastritis (AG), being the basic premalignant condition for the stomach cancer (SC), is commonly diagnosed and screened for by noninvasive biomarkers (pepsinogens, gastrin-17), however the data on those biomarkers at SC is inconsistent. Aim of investigation. To evaluate the markers of stomach atrophy along with risk factors of SC of different localization, histological type and stage in the «case series» study. Material and methods. Original investigation was designed as «case series», that included 85 patients with SC (48 m and 37 f, mean age 61.2±13,6 years) who were consistently referred to two medical institutions. All patients underwent interviewing the questionnaire concerning smoking and alcohol consumption, presence of gastroenterological symptoms and family history. Blood serum samples were analyzed using ELISA test kits «GastroPanel» («Biohit Plc», Finland). Manufacturer recommended threshold levels were used at diagnostics of AG. Results. The diagnosis of SC of the III to IV stage was established in 67.9% of patients. The most common location of the neoplasm was the stomach body (63,5%). Helicobacter pylori (H. pylori) infection was revealed by serological method in 74.1% of cases, of which in 15.1% the attempt of eradication treatment was carried out. In 90.6% of patients the adenocarcinoma of different differentiation grade was diagnosed, low degree of differentiation was the most common (57.6%). Signet-ring cell carcinoma was diagnosed in 7.1% of patients, undifferentiated tumor - in 2.4%. Pepsinogen-I (PGI) level under 50 mcg/l was found in 43.2% of patients, indicating different degrees of fundic atrophy. Significantly lower PGI scores were detected in SC patients with histologically verified atrophy. No significant differences in biomarker levels according to tumor location, histological type of SC and tumor stage were found. Conclusions. The «case series» study demonstrated high rate of late SC diagnostics with predominance of corpus location and the most malignant types. H. pylori infection was diagnosed in serologically in the most of patients, however attempts for eradication therapy was carried out only in 15% of patients. Fundic atrophy was diagnosed by serological tests in over 40% of patients, however no association with location, stage and morphological type of the tumor was established. Blood serum samples were analyzed using ELISA test kits «GastroPanel» («Biohit Plc», Finland). Manufacturer recommended threshold levels were used at diagnostics of AG.